A Wideband Rectenna Using High Gain Fractal Planar Monopole Antenna Array for RF Energy Scavenging - Mohammad M. Fakharian (International Journal of Antennas and Propagation)
This paper introduces a wideband rectenna that can scavenge ambient wireless power to a range of frequency band from 0.91 GHz to 2.55 GHz efficiently. The proposed rectenna is based on a wideband 2 × 2 fractal monopole antenna array with omnidirectional radiation patterns and high gains of 5 to 8.3 dBi at the desired bands. An improved two-branch impedance matching technique is presented which is designed to enhance the rectifier circuit performance with a relatively low input power ranging from −25 dBm to 10 dBm. Also, a full-wave wideband rectifier that can suitably improve the RF-to-DC power conversion efficiency is designed for the rectenna. A peak efficiency of 76%, 71%, 61%, and 62% is obtained at 950, 1850, 2100, and 2450 MHz, respectively. Measurement results show that a conversion efficiency of 68% has been achieved over an optimal 4.7 kΩ resistor when the simultaneous four-band input power level is −10 dBm. Moreover, an output DC voltage of around 243 mV with voltage varying within 160–250 mV can be achieved by gathering the low ambient wireless power inside laboratory. This study proves that the proposed rectenna can be applied to a range of many low-power electronic applications.